Sistem Sensor Detak Jantung Guna Mendukung Kebugaran Crew Saat Melaksanakan Dinas Jaga Mesin - Marchellinus Ivan H. P; Abdi Seno; Andy Wahyu Hermanto (Jurnal Informasi dan Teknologi, 2022)
The 2010 Manila Amendment Standard of Training Certification and Watchkeeping (STCW) regulation is to create and develop a system that can support the fitness of duty officers on duty. The officer's fitness is determined by the value of the heart rate at the start of watch duty. For that we need a system that can measure the heart rate quickly and precisely. This system must work effectively and accurately inform each officer's measurements. So this research was carried out with the aim of building an effective heart rate measurement. This system is supported by the Arduino Nano Microcontroller and an alarm system that provides information on the fitness of the officers. The method used is Research and Development which refers to ADDIE (Analysis, Design, Development, Implementation, and Evaluation). The result of this research is a heart rate measuring product that works very effectively. The required input consists of a grove-ear clip heart rate sensor as a heart rate detector in the form of a pulse signal and a vibrating DC motor with a buzzer as an alarm that generates a shock for the user of the device. The indications for this tool are using Bradycardia, Normal and Tachycardia heart conditions. So that this research is very much needed in supporting the testing of the fitness of tasks in carrying out the machine guard service properly and guaranteed.